KETERSEDIAAN INFRASTRUKTUR OLAHRAGA DAN DUKUNGAN PIMPINAN TERHADAP FREKUENSI PARTISIPASI OLAHRAGA - Triono, Sandi Dwi; Laksono, Agung (Jurnal Olahraga, 2017)
The background of this research is based on wanting to know the relationship between leadership support and infrastructure on the frequency of sports participation. It is important to realize that sports infrastructure and also support from leaders in facilitating it are urgently needed to conduct sports activities and are also expected to increase the frequency of sports participation, because without sports facilities and infrastructure it cannot develop. The purpose of this study was to determine how the influence of leadership support for sports infrastructure in increasing the frequency of sports participation. Data collection techniques are done by tests and observations. Data were analyzed descriptively qualitatively. The results of the study showed that not all of the infrastructure in STKIP Pasundan met the standards, but were already worth using. The leadership support has also been there but it is still not firm and makes the existing participants do not maximize the existing infrastructure because of the busy working time of the community.